ENERGY RECOVERY FOR CONTINUOUS DYEING PROCESS IN TEXTILE INDUSTRY ENTERPRISES - V. N. Romaniuk; D. B. Muslina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The paper ascertains and presents alteration in the energy consumption as a consequence of utilizing the low-temperature waste streams commonly used in the lines of continuous dyeing at the finishing shops of textile enterprises of Belarus. The utilization realizes through the engagement of lithium-bromide absorption heat pumps with various energy characteristics such as the heating coefficient (relative conversion ratio COPhp = 1,15; 1,7; 2,2) and the heating capacity. The latter associates with the converted heat-flow energy utilization variant with the heat-transfer medium heating system scheme (one-, twoand multistage heating). The article considers transition to previously not applied service-water preheating due to the technological acceptance of feeding higher temperature water into the dyeing machine and widening specification of the heattransfer media. The authors adduce variants of internal and external energy use and their evaluation based on the relative energy and exergy characteristics. With results of the thermodynamic analysis of the modernized production effectiveness the researchers prove that alongside with traditional and apparent interior utilization of the energy associated with the stream heat recuperation, it is advisable to widen the range of applied heat-transfer media. The transition to the service water twoand multi-stage preheating is feasible. The study shows that the existing energy supply efficiency extremely low index-numbers improve by one or two degrees. Since they are conditioned, inter alia, by the machinery design, traditional approach to energy supply and heat-medium usage as well as the enterprise whole heating system answering requirements of the bygone era of cheap energy resources. The authors examine the continuous dyeing line modernization options intending considerable investments. Preliminary economic assessment of such inevitable modernization options for the enterprise entire heat-and-power system shows reality of meeting all going with the times requirements such as economic, environmental, energy for similar projects.